Integrated Thematic Project-Based Learning Model for Soft Skills Development Using Content-Language Integrated Learning in Higher Education - Yulian, Ryani; Yuniarti; Ruhama, Ufi; Fitri, Nabila Nur; Rievaldy, Restu (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the low development of students' soft skills in the learning process in higher education, which tends to focus solely on cognitive aspects. This study aims to develop an integrated thematic Project-Based Learning (PjBL) model that aligns with the Content-Language Integrated Learning (CLIL) approach, where English is learned through specific course content to strengthen students' work skills. Using the ADDIE development model, a mixed method approach was used in this study involving 100 Management Study Program students and two English lecturers. Data were collected through a needs analysis based on Target Situation Analysis (TSA), a Likert scale survey validated with Cronbach's Alpha, and semi-structured interviews analyzed thematically. The expert evaluation recommended adding real case studies and more interactive activities. The final evaluation showed that integrating PjBL and CLIL effectively improved students' communication and soft skills. The results of this study indicate that the model can support curriculum development and improve students' readiness to face academic and professional demands. In conclusion, the development of integrated thematic PjBL with a language and CLIL can effectively train and strengthen students' soft skills in higher education. Implementing integrated thematic PjBL with a language and content-integrated learning approach can effectively support the development of students' soft skills in higher education, especially in collaboration, communication, and contextual problem-solving.